Towards an integrative view of AIS: using integrated business processes approach to framework the paradigm shift of AIS. (22nd May 2019) - Mohammad, Ahmed Ali; Saidi, Fethi; Abdulkarim, Mustafa Elkasih
The establishment of the inter-organisational paradigm across business has led to a new wave of process and information systems to stimulate the emerging trends. Analysis of the related literature often results in a large number of misconceptions. This paper attempts to give a coherent picture on how integrated business processes have transformed AIS from being information into knowledge system. In particular, the aim of our research is to introduce integrated businesses processes as a new approach for defining AIS. This paper empirically measures and analyses the determinants of IOAIS, as well as providing empirical evidence on how integrated business processes have technically supported new roles and contributions of such systems. Our empirical analysis leads to three main findings. First, our findings suggest that use of inter-organisational technologies has significant association with dynamic extension of AIS. Second, the inter-organisational technologies have transformed AIS through increasing interactivity and connectivity. Finally, these technologies also have led to real shift in the reliability and uses of accounting information, which in turn established knowledge contributions of AIS.